USE OF AN IMPROVED BUCKET ON A BULLDOZER (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The article describes the research work on improving the bulldozer wheel for digging hard and frozen soils. Proposals have been made to prevent the problems and excessive expenses that arise in the excavation of hard and frozen soil.